If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3 + 4)(5 * 5) = 0 Combine like terms: 3 + 4 = 7 (7)(5 * 5) = 0 Multiply 5 * 5 7(25) = 0 Multiply 7 * 25 175 = 0 Solving 175 = 0 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 8u+133=3u-2 | | f(x)=-x^2+14x-39 | | 13x^2+20x-92=0 | | f(x)=x^2+12x+37 | | f(x)=x^2+12+37 | | f(x)=x^2+12+3 | | n-2.5n-1.9=-2(n-1.3) | | f(x)=-x^2-12x-44 | | 5x-x=132 | | x+y=20xy=15 | | 5(x+8)-12=180 | | (2t^3+2)-(8t^2-3)+(5t^3+4t^2)=0 | | 760x^2+9049.07x-1583587.33=0 | | (3j^4+5)-(8j^3+5)-(6j^4+5j^3)=0 | | 3x+10y+0.5z=100 | | 3k^2+21k=0 | | x-1=99 | | 2(k+1)+2(1-9k)=y | | 5(10k+9)-7(1-4k)=y | | 74x+7= | | (2x^2+2x+18)+(3x^2-4x+13)-(x^2+15x-2)=0 | | 6(x-3)=-3x-54 | | f(x)=9x^2+54x+71 | | (5g^3+2)-(6g+6)-(4g^3-3g)=0 | | (7b^4-4)-(7b^3-5)+(4b^4-3b^3)=0 | | secx+cosx=0 | | 2r^2-10r-48=0 | | 3(9n+5)+8(10n-9)=y | | 4(3x-1)+9(-5x+2)=y | | 9(6a-10)+2(-6a+8)=y | | 6(4k-5)-4k=y | | -9(2-10a)+8a=y |